Yield loss of large cardamom (Amomum subulatum Roxb.) due to Colletotrichum blight in Sikkim - A K Biswas, M R Sudharshan, K A Saju, S Mech, T N Deka, U Gupta (Journal of Spices and Aromatic Crops, 2013)
Large cardamom (Amomum subulatum Roxb.) is affected by various fungal diseases. Of these, blight caused by Colletotrichum gloeosporioides (Penz.) Sacc. (perfect state Glomerella cingulata (Stoneman) spaulding & Schrenk) is one of the major production constraints. In order to assess the loss due to Colletotrichum blight, yield of affected plants of two cultivars, Varlangey and Sawney was recorded. Yields were also recorded from healthy plants of the same cultivars for comparison. There was 46.8% reduction in the dry yield of infected plants of Varlangey and 34.5% reduction in dry yield of Sawney as compared to healthy plants. The infected plants of Varlangey were found dead in the first year itself causing 100% loss. Lack of maturity of seeds, increased husk weight of fresh capsules and decreased weight of dried capsules were observed in the infected plants.